1980
DOI: 10.1056/nejm198001033020103
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Medical Care

Abstract: We analyzed data from the National Ambulatory Medical Care Survey to compare the style of practice of two primary-care providers, general internists and family-general practitioners. Whereas internists spent 18.4 minutes with the average patient, family-general practitioners spent 13.0 minutes. Whereas internists used laboratory tests in 73 per cent of visits and x-ray tests in 53 per cent, family-general practitioners used these studies in 34 and 19 per cent of visits. Internists provided instructions regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Family practitioners included CHD in their differential diagnosis, but were significantly more likely to rank a psychosocial cause above CHD, express more certainty with that formulation, and recommend psychosocial and behavioral interventions. These findings are consistent with those from other studies (Cherkin et al, 1987; Noren et al, 1980; Smith & McWhinney, 1975) and are likely driven by the differing levels of certainty on the primary diagnosis of CHD (Lutfey, Link, Grant, Marceau, & McKinlay, 2009). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Family practitioners included CHD in their differential diagnosis, but were significantly more likely to rank a psychosocial cause above CHD, express more certainty with that formulation, and recommend psychosocial and behavioral interventions. These findings are consistent with those from other studies (Cherkin et al, 1987; Noren et al, 1980; Smith & McWhinney, 1975) and are likely driven by the differing levels of certainty on the primary diagnosis of CHD (Lutfey, Link, Grant, Marceau, & McKinlay, 2009). …”
Section: Discussionsupporting
confidence: 91%
“…That variations may also occur within a medical specialty, for example between general internists and family practitioners within primary care, has received little attention. What occurs at the level of primary care is important for several reasons; a) it is the gateway to the healthcare system, crucially determining the course of many diseases, costs and patient outcomes; b) it is where the vast majority of illness in society is presented and cared for; c) it may be the point of origin for the generation and amplification of many reported disease disparities; (McKinlay et al, 2007; McKinlay, Potter, & Feldman, 1996) and d) it may also be the point of origin for ever increasing costs of health care, given the suggestion that the most expensive piece of medical technology may be a physicians’ pen (Gawande, 2009; Noren, Frazier, Althman, & DeLozier, 1980). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limited literature on PCP-related variation in screening, the existing evidence about differing quality of preventive health care among PCPs [15-18] suggests that similar differences in quality of CRC screening may contribute to underuse of screening in some populations. One study, which included analyses on CRC testing by PCP specialty, found that patients receiving their usual routine care from family/general practitioners were less likely to have had CRC testing than those receiving care from a general internists [18].…”
Section: Introductionmentioning
confidence: 99%